Role of knowledge, financial capital and business performance in foodservice sector - Sorayah Nasip; Ramraini Ali Hassan; Stephen Laison Sondoh Jr. (Asian Academy of Applied Business, 2019)
This research aims to investigate the relationship between knowledge, financial capital and business performance in the foodservice sector. A total of 336 entrepreneurs from Kota Kinabalu, Sabah have participated in the study. The data were analysed using Partial Least Square (PLS) technique version 2.0. The results have shown that knowledge and financial capital are positively related to business performance among entrepreneurs. This research might give some views among entrepreneurs to improve their business performance. The findings of the research may extend existing knowledge in the business performance discipline as well as to impart valuable information to policymaker in strengthening and assists suitable support to entrepreneurs to sustain in the marketplace. Therefore, knowledge and financial capital are important indicators to predict business performance among entrepreneurs.